First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

Chemoselective ring closure of 4-(3-Methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal leading to pandalizine A - Yadav, Mahesh B.; Pandhade, Kailas R.; Argade, Narshinha P. (ACS Omega, 2020)
Starting from methylmaleic anhydride, a facile total synthesis of pandalizine A alkaloid is described via the regioselective reduction of methylmaleimide and acid-catalyzed enolization of 4-(3-methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal followed by chemoselective intramolecular dehydrative cyclization as the key steps. It is noteworthy that the analogous model system with an additional beta-methyl group followed an alternative chemoselective intermolecular aldol condensation pathway.